Dermatological findings in SARS‐CoV‐2 positive patients: An observational study from North India. Issue 6 (6th July 2020) - Dalal, Ashish; Jakhar, Deepak; Agarwal, Vishal; Beniwal, Ravi
Abstract: A novel coronavirus (severe acute respiratory syndrome corononavirus‐2; SARS‐CoV‐2) has affected millions of people across the world. The coronavirus disease (COVID‐19) resulting from SARS‐CoV‐2 manifests in variable clinical severity, featuring both respiratory and extra‐respiratory symptoms. Dermatological manifestations of COVID‐19 are sparsely reported. To study the various dermatological findings in SARS‐CoV‐2 positive patients in Indian population. Institutional ethical committee permission was sought and102 SARS‐CoV‐2 positive patients were included in the study. A thorough clinical examination was done to determine the nature and frequency of various dermatological manifestations in these patients. Out of the 102 positive cases, 95 were males. The mean age of the group was 39.30 years. Thirteen patients (12.7%) were found to have dermatological manifestations. Three (2.9%) had maculopapular rash, two (1.9%) had urticarial lesions and eight (7.8%) patients had itching without any specific cutaneous signs. Trunk was the most frequently affected area, followed by the extremities. No mucosal signs and symptoms were detected. Dermatological manifestations were seen in a small group of COVID‐19 patients. The presentation may vary in different population groups and based on severity of disease.